Geometry, oblique kinematics and extensional strain variation along a diverging plate boundary: The example of the northern Theistareykir Fissure Swarm, NE Iceland - Bonali, FL; Tibaldi, A; Pasquaré Mariotto, F; Saviano, D; Meloni, A; Sajovitz, P (Tectonophysics, 2019)
The boundary between the American and European plates emerges in Iceland, an outstanding natural laboratory where it is possible to analyse ongoing rifting processes. In the North Volcanic Zone, we studied with unprecedented detail an active rift, known as the Theistareykir Fissure Swarm (ThFS). We surveyed an area of 85 km2 with 694 measurement sites along 1537 post-Late Glacial Maximum extension fractures. In the southern sector of the study area, fractures strike N30–40° with opening directions about N120°. Fractures in the central sector strike about N00° and opening directions are N90–100°. In the northern sector, fractures strike about N30° with opening directions about N125°. Through a comparison with older faults cropping out in the substrate at the shoulder of the ThFS, we are able to suggest that variations in fracture strike are the effect of substrate structural inheritance as well as the possible interaction with the Tjörnes Fracture Zone. With regard to kinematics, we highlight that most fractures show a small, but systematic, strike-slip component (a more frequent right-lateral component and a less common, left-lateral one). This cannot be explained as the result of fracture strike rotation relative to the regional, tectonic least principal stress. We conclude that the net opening directions can result from the combination of tectonic offsets and events caused by shallow magma chamber inflation and/or dyke intrusions. The latter can produce transcurrent components of displacement along new or already existing fractures